Medicine and social justice : essays on the distribution of health care - Rhodes, Rosamond; Battin, M. Pabst; Silvers, Anita (Oxford University Press, 2002)
Because medicine can preserve and restore health and function, it has been widely acknowledged as a basic good that a just society should provide its members. Yet there is wide disagreement over the scope of what is to be provided, to whom, how, when and why. In this uniquely comprehensive book some of the best-known philosophers, doctors, lawyers, political scientists, and economists writing on the subject discuss the concerns and deepen our understanding of the theoretical and practical issues that run through the contemporary debate. The first section lays a broad theoretical basis for understanding the subject of justice, particularly as it relates to the distribution of health care. The second section critically examines how medical care is distributed in different countries around the world and the particular advantages and injustices associated with those systems. The third section draws attention to the special needs of different social groups and the specific issues of justice that are raised by the impact of various policies on health care distribution.; The concluding section delves into the dilemmas that confront those designing health care systems - the politics, the priorities, and the place of desires as opposed to needs in a socially just scheme.